Characteristics of Addictive Status in Women with Disorders in Gender-Role Behavior of Non-Transsexual Type And Alcohol Addiction - Archipenko, Y. P. (Psychiatry, Neurology and Medical Psychology, 2015)
Eighty eight (88) women OF 18–27 years old (average age 22.50 years) with alcohol addiction and deviations of gender-role behavior (treatment group) in-patient patients in Regional Clinical Psychiatric Hospital No.3 and Kharkov Regional Clinical Narcological Hospital in 2012–2014 as well as 30 healthy women (average age 30,00 years) residents of Kharkov and Kharkov region without signs of addiction and deviations of gender-role behavior (reference group) have been studied. Addicted women with genderrole deviations of non-transsexual behavior were found to have complex addictive profi le that can be shown by: dominant pathologic (nosologic) pattern of alcohol consumption; presence of two prenosological patterns of consumption of psychoactive substances (PAS) of diff erent hazardous level (‘relatively safe’ and ‘hazardous’) alone with nosologic patterns; presence of two types of PAS consumption (mono-substance and poly-substance); consumption of two illegal PAS (cannabinoids). Such factors as earlier beginning of alcohol consumption, shorter period of inebriety, earlier age of the fi rst degree of alcohol addiction, shorter duration of stages of disorder, higher initial tolerability and its increase, increased incidence of altered state of alcohol intoxication starting from the alcoholism II degree in women with gender-role transformation compared to hyperrole women allow considering clinical course of alcohol addiction in women with gender-role transformation as more malignant.